Inefficacy of n-acetylcysteine in mitigating cue-induced relapse to amphetamine - Fort, Troy D. (Kansas State University, 2022)
Glutamatergic imbalances are characteristic of SUDs. Glutamate is maintained by a combination of astrocytic and neuronal transporters within the nucleus accumbens (ACb) and medial prefrontal cortex (mPFC) and disruptions in this homeostasis engender SUD. One transporter, the cysteine-glutamate exchanger (xCT), is primarily localized on astrocytes and helps maintain glutamate concentrations. This process is disrupted by cocaine use, and the therapeutic N-acetylcysteine (NAC) lowers cue-induced relapse to cocaine by restoring xCT function. However, little research has shown how these effects extend to other psychostimulants, such as amphetamine (AMP). In the present study, we assessed disruption of astrocytic xCT expression following AMP-induced cue seeking, and the degree to which NAC can attenuate relapse via changes to astrocyte and xCT expression. To test this question, we administered NAC (100 mg/kg ip) daily during a 14-day abstinence period following completeion of amphetamine self-administration. Cue-induced relapse was tested following one (WD1) and 14 days (WD14) of withdrawal in separate subsets of animals. We then assessed expression of xCT and astrocyte densities in the mPFC and ACb. During the relapse test, cue-induced responding was higher in AMP-treated rats compared to saline-treated rats. NAC failed to attenuate relapse at either WD 1 or WD 14. Histology indicated that rats exposed to AMP had increased astrocyte expression in the mPFC and ACb when compared AMP-naïve rats. Repeated injection with NAC decreased xCT expression within regions of the mPFC and ACb only in animals with AMP exposure. Overall, these results suggest that NAC may be an ineffective treatment option for lowering cue-induced relapse to AMP. Further, the results suggest that stimulating xCT via NAC may not be an effective therapeutic approach for decreasing cue-seeking for AMP.
Keywords: Astrocytes; Glutamate; Relapse; Craving; Amphetamine